PEMANFAATAN LIMBAH SERBUKKAYU MAHANG(Macaranga sp.) DENGAN PENAMBAHAN CANGKANG KAKAO (Theobroma cacao L.) MENJADI BRIKET SEBAGAIBAHAN BAKAR ALTERNATIF - Juniati Lampita Sinaga; Rudianda Sulaeman; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Charcoal briquettes is one type of eco friendly fuels that can be renewed. Briquettes can be made by utilizing waste of biomass, including mahang wood sawdust waste and cacao shells. Utilization of those wastes is to determine whether the wastes can be utilized as biomass energy to reduce the negative impacts of waste from forest products. This study aims to create and determine the characteristics of briquettes from mahang wood sawdust waste and cacao shells. This research used completely randomized design method which is consisted of three treatments and three replications. The results showed that mahang wood sawdust and cacao shells can be used as raw material for the manufacture of charcoal briquettes. The average results obtained moisture content about 24, 89%-29.33%. The average calorific value 4529.68 cal/gram-5064.32 cal/gram, treatment P2 and P3 have met the criteria of SNI. The average power calculation is the fuel of 0.22 gram/minute-0.26 gram/minute Keywords: Briquettes, biomass, alternative, mahang wood sawdust, cocoa shells